Analisis Pengaruh Return On Asset, Debt To Equity Ratio, Total Asset Turnover dan Net Profit Margin Terhadap Return Saham Pada Perusahaan Sub Sektor Perdagangan Besar yang Terdaftar di BEI Periode 2012 – 2016 - Sherli Desti Pratiwi (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2020)
This study aims to examine and analyze the effect of Return On Asset, Debt to Equity Ratio, Total Assets Turnover, and Net Profit Margin to Stock Return on sub-sector trading company listed on the Indonesia Stock Exchange for the period 2012-2016. The analysis method used is Data Panel Regression. The population in this study are all companies included in the trading company sub-sectors listed on the Bursa Efek Indonesia for the period 2012-2016, as many as 32 companies. Determination of the number of samples was carried out using purposive sampling technique and determined by 20 companies. The results of this study showed that TATO had no effect on Stock Return. However, ROA, DER and NPM has a positive effect on Stock Return.